Measures of diabetic retinopathy treatment coverage: protocol for a methodological review - Stuart Keel; Matthew J Burton; Jacqueline Ramke; Iris Gordon; Jennifer Evans; Nyawira Mwangi; Covadonga Bascaran; Rinki Murphy; Pushkar Raj Silwal; Subash Bhatta; Nayana Pant; Nimisha Chabba (BMJ Open)
Introduction Diabetic retinopathy is one of the leading causes of vision impairment globally. Alongside the systemic control of diabetes and timely detection of diabetic retinopathy, the prompt initiation and completion of treatment is essential to prevent vision loss. Routine monitoring of access to retinal screening services for the detection of diabetic retinopathy is common, while monitoring of coverage of subsequent treatment services is far less common. When diabetic retinopathy treatment coverage is assessed, there is great variability in how it is defined and reported. If a definition of treatment coverage could be standardised, the monitoring of the quality of diabetes eye care could more readily be compared between settings and over time. The aim of this review is to summarise how diabetic retinopathy treatment coverage has been measured in published studies and the extent to which these have been disaggregated by population groups.Methods and analysis A search will be conducted on Medline and Embase without any language restrictions, for cohort and cross-sectional studies published from 1 January 2015 that report diabetic retinopathy treatment coverage for adults with diabetic retinopathy and/or macular oedema. We will include studies from any world region reporting diabetic retinopathy treatment coverage for one or more of: (1) laser photocoagulation; (2) intravitreal injections of antivascular endothelial growth factor agents; (3) intravitreal injections of corticosteroids; (4) vitrectomy. The PROGRESS framework (place of residence, race/ethnicity/culture/language, occupation, gender/sex, religion, education, socioeconomic status and social capital) will be used to assess disaggregation by population groups. Two investigators will independently screen studies and extract relevant data. Data will be synthesised descriptively to outline the full range of definitions of diabetic retinopathy treatment coverage in the literature and identify the common sources of data used.Ethics and dissemination This review will only include published data; thus, no ethical approval will be sought. The findings of this review will be published in a peer-reviewed journal and presented at relevant conferences. The findings will also be considered in conjunction with an ongoing review on retinal screening for diabetic retinopathy to develop indicators for monitoring of services along the diabetes eye care pathway, which may include an indicator of effective service coverage.Registration Open Science Framework registration 6/08/2024: https://osf.io/5b93m